CORRECTING STUDENTS CORRECTLY: AVOIDING GRAMMAR MISCONCEPTIONS IN THE FOREIGN LANGUAGE CLASSROOM: Received: 18th July 2023; Revised: 02nd August 2023, 12th September 2023; Accepted: 14th September 2023 - Hull, Todd (PUPIL: International Journal of Teaching, Education and Learning, 2023)
Grammatical accuracy is a justifiable goal in language teaching classrooms. But misconceptions about grammar can hinder this goal. The main misconception is that native speakers make grammar errors when using their own native language. They do not. The idea that native speakers can make grammar mistakes in their own languages is detrimental to foreign language classrooms because when language teachers attempt to find answers to grammar questions, they encounter conflicting information and are sometimes not able to give their students useful answers. The main cause of the misconception that native speakers can make grammar errors in their own language is the conflation of formal and informal style, a conflation of grammar and style, which leads to informal usage being incorrectly stigmatized as incorrect grammar. This paper will outline three major misconceptions arising from this fundamental confusion of style and grammar: 1) the idea that native speakers use words incorrectly; 2) native speakers using words that are said not to be real words; and 3) conflation of emphasis and redundancy. This issue will be addressed in the context of the English language. But the principles apply across languages. Knowledge of these misconceptions will allow language teachers to answer and advise students.